Chemical Vapor Deposition of Silicon Carbide and Titanium Nitride on continuous carbon fibres as a protective layer in Metal Matrix Composites - Popovska, Nadejda; Gerhard, Helmut; Emig, Gerhard; Wurm, Doris; Singer, Robert (Vol. 22: Advanced Structural Fiber Composites - III, Proceedings of Topical Symposium V "Advanced Structural Fiber Composites" of the Forum on New Materials of the 9th CIMTEC-World Ceramics Congress and Forum on New Materials, 1999)

Chemical vapor deposition of titanium nitride on carbon fibres as a protective layer in metal matrix composites - Popovska, Nadejda; Gerhard, H.; Wurm, Doris; Poscher, S.; Emig, Gerhard; Singer, Robert (Materials & Design, 1997)
The significance of carbon fibres for reinforcing metals has increased in the last years, because of their excellent mechanical properties. However, to avoid the weakening reaction during MMC fabrication between the fibre and the liquid metal, a protective coating has to be applied. Continuous carbon fibre roving with 6000 filaments were coated with TiN by thermal induced chemical vapour deposition (CVD) using a gas mixture of TiCl4, N2 and H2 as a precursor. The deposition process in the reactor was simulated by a modified Phoenics-CVD software program using a 2D-axisymmetric model. Carbon fibres reinforced magnesium matrix composites are fabricated by a pressure infiltration casting process. The mechanical properties of the MMCs can be used to demonstrate the efficacy of the coated fibre approach. The rule of mixture is realized to 98/ for the coated fibre, and only 48% for the uncoated system. The infiltration pressure during the processing of composites was lowered from 10 to 1 MPa for the TiN coated syste
Keywords: Carbon fibres; Metal matrix composites; Reinforcing metals; Titanium nitride

Detailed 3D-simulations of single phase reacting flow in randomly packed beds with low aspect ratios - Freund, Hannsjörg Dieter; Klemm, Elias; Emig, Gerhard; Zeiser, Thomas; Brenner, Gunter; Durst, Franz (Chemie Ingenieur Technik, 2001)
UnivIS-Import:2015-03-09:Pub.2001.tech.ITC.stmmec.detail

Detailed simulation of transport processes in fixed-beds reactors - Emig, Gerhard; Zeiser, Thomas; Freund, Hannsjörg; et al. (Industrial & Engineering Chemistry Research, 2005)
UnivIS-Import:2015-03-09:Pub.2005.zwiss.rrze.zensys.detail

Magnesium-Matrix-Verbundwerkstoffe mit CVD-TiN-beschichteten Kohlenstoffasern - Wurm, Doris; Singer, Robert; Popovska, Nadejda; Gerhard, H.; Emig, Gerhard (Verbundwerkstoffe und Werkstoffverbunde, 1997)